INVESTIGATION OF BENTONITE CLAY SURFACE AS A PHYSICAL ANTIDOTE IN ADSORPTION OF AMITRIPTYLINE-HCl, CHLORPROMAZINE-HCl AND CHLORDIAZEPOXIDE-HCl FROM SOLUTION - A. ISA, SAADOON; M. JASSIM, SAMEER; K.A. HUSSEIN, HUSSEIN (Iraqi Journal of Pharmaceutical Sciences, 2017)
A detailed study of adsorption from solution of amitriptyline-HCl, chlorpromazine-HCl andchlordiazepoxide-HCl on bentonite clay surface has been performed at variable conditions oftemperature, pH and ionic strength. It is aimed in this work to explore the capability of this clay intreatment of poisoning by the mentioned drugs if taken in quantities higher than the usual doses.Quantities of drugs adsorbed have been determined by UV spectrophotometric technique. Thesequence of adsorption in neutral media at 37.5 CÙ’ followed the order:Amitriptyline-HCl > chlorpromazine-HCl > chlordiazepoxide-HCl.The results were discussed in the light of Langmuir and Freundich adsorption isotherms. The usualbasic themodynamic functions were estimated.